Implementing mahalanobis-taguchi system and time-driven activity- based costing for capacity utilization in academic faculty - Sri Nur Areena, Mohd Zaini (2024)
In modern society, system integration that enables multiple sub-systems to function as one is emerging in various fields like industry, commerce, and infrastructure. Without a complete framework for modelling, analysis, and optimization of system integration process, the role of system integration could be unsatisfactory. Currently, the organization of university was guided based on annual achievement assessment report (Laporan Penilaian Prestasi Tahunan, LNPT) to determine academicians’ performance. All academician need to fill their Annual Work Target (AWT) and conduct self evaluation before another assessment using Likert scale is made. Thus, the current assessment practised human judgement with hints of implicit or unconscious bias against one person, especially in a way considered to be unfair. Moreover, the current framework of system is based mainly on quality element only. Hence, a system integration framework which relies on stand alone quality element is deficient. In order for an integrated system to be sustainable, multiple management system should act complementary wherever possible. The first objective of this work is to investigate the degree of contribution and capacity utilization in academic performance. Next, the second objective is to propose frameworks by considering quality and cost for system integration. Lastly, the final objective is to validate effectiveness of the system integrations. This work is conducted at Faculty of Manufacturing and Mechatronic Engineering Technology (FTKPM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA). The samples are divided into two types which are grade DS45 and DS51/52. As a result of measurement of the abnormality from Mahalanobis distance determination, normal and abnormal samples have been identified and illustrated in the scatter diagrams. In view of diagnosis of degree of contributions for each parameters, in order to obtain lower Mahalanobis distance or closer to normal group, positive degree of contribution should be decreased, while negative degree of contribution should be increased. Meanwhile, commensurate to the capacity utilization analysis, the used and unused capacity of both time and cost for every samples are proportionately determined. Three samples from each grade DS45 and DS51/52 are selected to be categorized as poor, moderate, and good performance. There are four proposed frameworks for this work’s system integration. They are conventional-ABC integration, conventional- TDABC integration, MTS-ABC integration, and MTS-TDABC integration. For the implementation of system integration, 53 parameters from quality element will reflected to 35 sub-activities from costing model. In order to validate all proposed system integrations, a sample from grade DS51/52 is chosen. Following the calculations, the total used cost of every integrations are achieved and subsequently been compared. The total used cost that nearly close to the actual supplied capacity is considered the best. From the validation, MTS-TDABC integration is proven the ideal model because the used cost is MYR 69,521 which nearest to the actual supplied resource cost of MYR 70,260. The proposed frameworks will impact the education environment by integrating the significant parameters using Mahalanobis-Taguchi System (MTS) and sub-activities using Time-Driven Activity-Based Costing (TDABC). In the future, a possible study can be conducted using similar model and mechanism in different higher education institution environment such as evaluating undergraduate students, non-academic staffs, medical personnel in university health center, and many more. The analysis should be further tested with cases that deal with high accessibility and transparency of information.